SPECIFIC FEATURES OF INDUSTRIAL DEVELOPMENT IN UZBEKISTAN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This in the article our country industry network, it to oneself typical aspects, 2024 first half indicators and in the field there is problems, to them conclusion and offers given.